PENGARUH PEMASARAN RELASIONAL DAN LAYANAN PURNA JUAL TERHADAP KEPUASAN PELANGGAN SERTA DAMPAKNYA TERHADAP NIAT BERPERILAKU (STUDI KASUS DI PT ATLAS COPCO NUSANTARA) - Rubiati Fadhilah (Operations Excellence: Journal of Applied Industrial Engineering, 2014)
Abstract. The phenomenon, as object of research is behavioral intentions ofcustomers to the products indicated influenced by customer satisfaction. Customersatisfaction is predicted to be affected by the company's performance-relatedimpairment of relational marketing and after-sales service research objective wasto analyze the effect of relationship marketing and after-sales service to thecustomers behave intentions through customer satisfaction. The method used isquantitative research approach. The research sample of 100 respondents drawnfrom the study population of 100 people by using census method. Data collectiontechniques using literature study, questionnaire and observation techniques.Analysis of data using realiabilitas validity test instruments, test the classicalassumption of normality test and heterokedastisitas as well as analysis andhypothesis testing two lanes. The results showed that the relationship marketingand after sales service significantly affect partially or simultaneously on customersatisfaction. In addition, the results of this study also showed that the relationshipmarketing and customer satisfaction partially significant affect on the behavioralintentions but after sales service does not significant affect on behavioralintention. Furthermore, in the future research is recommended to include othervariables such as price, company's image, etc.Keywords: relationship marketing, after sales service, customer satisfaction,behavioral intentions.